Droplet digital PCR quantification of norovirus and adenovirus in decentralized wastewater and graywater collections: Implications for onsite reuse. (1st February 2020) - Jahne, Michael A.; Brinkman, Nichole E.; Keely, Scott P.; Zimmerman, Brian D.; Wheaton, Emily A.; Garland, Jay L.
Abstract: Risk-based treatment of onsite wastewaters for decentralized reuse requires information on the occurrence and density of pathogens in source waters, which differ from municipal wastewater due to scaling and dilution effects in addition to variable source contributions. In this first quantitative report of viral enteric pathogens in onsite-collected graywater and wastewater, untreated graywater (n = 50 samples) and combined wastewater ( i.e., including blackwater; n = 28) from three decentralized collection systems were analyzed for two norovirus genogroups (GI/GII) and human adenoviruses using droplet digital polymerase chain reaction (ddPCR). Compared to traditional quantitative PCR (qPCR), which had insufficient sensitivity to quantify viruses in graywater, ddPCR allowed quantification of norovirus GII and adenovirus in 4% and 14% of graywater samples, respectively (none quantifiable for norovirus GI). Norovirus GII was routinely quantifiable in combined wastewater by either PCR method (96% of samples), with well-correlated results between the analyses (R 2  = 0.96) indicating a density range of 5.2–7.9 log10 genome copies/L. These concentrations are greater than typically reported in centralized municipal wastewater, yet agree well with an epidemiology-based model previously used to develop pathogen log-reduction targets (LRTs) for decentralized non-potable water systems. Results emphasize the unique quality of onsite wastewaters, supporting the previous LRTs and further quantitative microbial risk assessment (QMRA) of decentralized water reuse. Graphical abstract: Image 1 Highlights: New ddPCR application for virus quantification in wastewater and graywater. Improved sensitivity relative to qPCR allows greater quantification frequency. Measured concentrations agree well with previous epidemiology-based simulation. Results support published pathogen reduction targets for onsite non-potable reuse.